Islamic Education Curriculum Innovation in the Digital Era: Challenges and Opportunities - Mukarom, Zaenal; Darmawan, Deni; Agustin, Mubiar; Dwijantie, Jeane Siti; Samadi, Mochamad Ramdan (International Education Trend Issues, 2024)
This research aims to explore and identify innovations in the Islamic education curriculum in the digital era, focusing on the challenges and opportunities faced in its implementation. The development of digital technology has brought significant changes to the world of education, including Islamic education. This study uses a qualitative approach with a literature study method. The results of the study show that innovations in the Islamic education curriculum in the digital era must include the integration of technology that is in line with Islamic values, the development of digital competencies for educators, and the update of the curriculum that is flexible and adaptive to technological changes. The study also found that despite significant challenges, such as resistance to change and limited resources, the opportunities to improve the quality of Islamic education through technology are enormous. With the right approach, digital technology can be used to enrich learning, expand access to education, and build a generation of digitally competent Muslims who are firm in Islamic values.